Intraoperative radiotherapy for brain metastases: first-stage results of a single-arm, open-label, phase 2 trial - Castro, Douglas Guedes de; Sanematsu, Paulo Issamu; Pellizzon, Antônio Cassio Assis; Suzuki, Sérgio Hideki; Fogaroli, Ricardo Cesar; Dias, José Eduardo Souza; Gondim, Guilherme Rocha Melo; Estrada, Daniel Alvarez; Silva, Maria Letícia Gobo; Rassi, Marcio Saquy; Chen, Michael Jenwei; Giacomelli, Richard; et al. (Journal of neuro-oncology, 2023)
Focal stereotactic radiosurgery to the surgical cavity lowers local recurrence after resection of brain metastases (BM). To evaluate local control (LC) and brain disease control (BDC) after intraoperative radiotherapy (IORT) for resected BM.
Online veröffentlicht: 24. Februar 2023
Gesehen am 18.07.2024